Undergraduates at a Research University Think of Faculty as Teachers and That Teaching is Prestigious. (January 2020) - Morling, Beth; Lee, Jeong Min
What do university students understand about faculty work? Undergraduate (mostly first-year) students ( N = 317) at a research university gave definitions of tenure, estimated how much time faculty spend teaching, and rated fictional faculty members. Most students could define tenure but could not describe how it is earned or its role in academic freedom. Students overestimated the time faculty spend on teaching and underestimated time spent on research. Finally, students who assumed that fictional faculty taught more courses also assumed they had higher status. By comparison, faculty respondents ( N = 645) who read the same fictional descriptions assumed higher teaching loads went with lower status markers. As they acculturate to life at a research university, first-year students could benefit from learning about faculty research roles and the value of academic freedom.